PENGARUH KARAKTERISTIK INDIVIDU, BUDAYA, DAN KOMUNIKASI TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI KECAMATAN BATULICIN KABUPATEN TANAH BUMBU - Eddy Sukharwadi (KINDAI, 2020)
This research aims to; (1) knowing and analyzing the influence of individual characteristics, culture, and communication simultaneously on community participation in village development in Batulicin Subdistrict, Tanah Bumbu District, (2) knowing and analyzing the influence of individual characteristics, culture, and communication partially on community participation in development Villages in Batulicin Subdistrict, Tanah Bumbu Regency, and (3) find out and analyze the dominant influence of individual, cultural, and communication characteristics variables on community participation in village development in Batulicin Subdistrict, Tanah Bumbu District. This research is an explanatory research with this type of research is causal associative. The population in this study is the Village apparatus in Batulicin District, Tanah Bumbu Regency. The number of samples in this study were 100 respondents. The technique of determining the sample using proportional random sampling. The type of research data used is quantitative and qualitative, while the data sources used are primary and secondary data. Data collection techniques through interviews, questionnaires, and documentation. The data analysis technique uses multiple linear regression models. Based on the results of the analysis show that individual characteristics, culture and communication simultaneously affect community participation in the development of the Village in Batulicin District, Tanah Bumbu Regency. Partially, individual characteristics, culture and communication influence community participation in village development in Batulicin District, Tanah Bumbu Regency. Individual characteristics are the dominant variables that affect individual characteristics, culture and communication affect community participation in village development in Batulicin District, Tanah Bumbu Regency. Keywords: Individual Characteristics, Culture, Communication, community Participation in Village Development